Mercy Watson : something wonky this way comes - DiCamillo, Kate (DiCamillo, Kate. Mercy Watson collection, 2009)
When Mr. and Mrs. Watson and their pig Mercy take in a movie at the Bijou Drive-In, mayhem ensues after Mercy smells the enticing scent of hot buttered popcorn.